Reading the world through the educational curriculum: The Social Sciences curriculum in Brazil in the context of the rise of conservatism - Amurabi Oliveira (Universitat Autònoma de Barcelona, 2021)
In Brazil, the growing political polarization that culminated in the election of Jair Bolsonaro in 2018 consolidated a shift in educational policy that had already been pointed out in previous years, as demonstrated by the Nonpartisan school movement performance. In this article, we analyze the curriculum of human and social sciences in secondary education in Brazil from the Brazilian Learning Standards, and how that document reflects the rise of these conservative movements. On the one hand, it was observed that important categories for the social sciences, such as gender, were removed, thus removing the centrality of categories such as racism and social inequalities; on the other hand, there is a strong dispute over the meanings of other concepts, such as human rights. Both actions converge to fine-tune the human and social sciences curriculum with the guidelines of conservative movements in the educational field.